A Guide for Oncologic Patient Management during Covid-19 Pandemic: The Initial Experience of an Italian Oncologic Hub with Exemplificative Focus on Uro-Oncologic Patients - Francesco A. Mistretta (Cancers, 2020)
The recent exponential increase in the number of COVID-19 patients in Italy led to the adoption of specific extraordinary measures, such as the need to convey treatment of all non-deferrable cancer patients to specialized centres (hubs). We reported a comprehensive summary of guidelines to create and run an oncologic hub during the COVID-19 pandemic. Oncologic hubs must fulfil some specific requirements such as a high experience in oncologic patient treatment, strict strategies applied to remain a “COVID-19-free” centre, and the creation of a dedicated multidisciplinary “hub team”. Cancer treatment of patients who belong to external centres, namely spoke centres, could be organized in different pathways according to the grade of involvement and/or availability of the medical team of the spoke centre. Moreover, dedicated areas should be created for the management and treatment of patients who developed COVID-19 symptoms after hospitalization (i.e., dedicated wards, operation rooms and intensive care beds). Lastly, hospital staff must be highly trained for both preventing COVID-19 contagion and treating patients who develop the infection. We provided a simplified, but complete and easily applicable guide. We believe that this guide could help those clinicians who have to treat oncologic patients during the COVID-19 pandemic.